2020
DOI: 10.1038/s41598-020-77157-0
|View full text |Cite
|
Sign up to set email alerts
|

Patulin suppresses α1-adrenergic receptor expression in HEK293 cells

Abstract: Patulin (PAT) is a common mycotoxin contaminant of apple products linked to impaired metabolic and kidney function. Adenosine monophosphate activated protein kinase (AMPK), abundantly expressed in the kidney, intercedes metabolic changes and renal injury. The alpha-1-adrenergic receptors (α1-AR) facilitate Epinephrine (Epi)-mediated AMPK activation, linking metabolism and kidney function. Preliminary molecular docking experiments examined potential interactions and AMPK-gamma subunit 3 (PRKAG3). The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…Cells were treated with 10 or 20 μM of patulin for 24 h, and cell death was determined by trypan-blue exclusion assay. The concentrations chosen were within the range used in previous studies done on similar cell lines, and they are also within the range that is encountered in cases where exposure is beyond the maximum recommended limits in humans ( Pillay et al, 2020 ; Zhang et al, 2015 ; Zhong et al, 2018 ; Zhou et al, 2010 ). Compared to cells expressing Nrf1a, knockout cells showed decreased survival after treatment with patulin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were treated with 10 or 20 μM of patulin for 24 h, and cell death was determined by trypan-blue exclusion assay. The concentrations chosen were within the range used in previous studies done on similar cell lines, and they are also within the range that is encountered in cases where exposure is beyond the maximum recommended limits in humans ( Pillay et al, 2020 ; Zhang et al, 2015 ; Zhong et al, 2018 ; Zhou et al, 2010 ). Compared to cells expressing Nrf1a, knockout cells showed decreased survival after treatment with patulin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…43 Thus, GSH depletion inhibits drug efflux by MRP, increases intracellular drug accumulation, and reverses drug resistance. 42,44 Furthermore, GSH is synthesized via two consecutive ATP-dependent reactions, 32 and GSH depletion influences GSH synthesis. A negativefeedback mechanism like this is conducive to reversing drug resistance in tumors.…”
Section: Journal Of Materials Chemistry B Reviewmentioning
confidence: 99%
“…Thus, intracellular GSH content affects mitochondrial function, such as electron transport chain function 41 and adenosine triphosphate (ATP) production. 42 The high expression of multidrug-resistance proteins, which are ATP-dependent efflux pumps with a broad substrate specificity, is one of the most common reasons for multiple-drug resistance (MDR). 43 Thus, GSH depletion inhibits drug efflux by MRP, increases intracellular drug accumulation, and reverses drug resistance.…”
Section: The Role Of Key Ferroptosis-regulated Molecules In Tumor Dru...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found PAT induced oxidative DNA damage in HEK293 kidney cells, leading to renal injury by targeting the α-adrenergic receptors expressed in the kidneys (Hering et al 2020 ; Pillay et al 2020 ). These receptors are activated by endogenous catecholamines (Michelotti et al 2007 ) and engage in signal transduction through the extracellular signal-regulated kinases/mitogen-activated protein kinases (ERK/MAPK) and phosphatidylinositide-3-kinase/protein kinase B (PI3K/AKT) signalling pathways (Karkoulias et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%